Impact of Chlorella vulgaris biomass substitution on in vitro bioaccessibility of cookies - Dündar, Ayşe Neslihan; Aygün, Ahmet; Şahin, Oya Irmak (International Society of Academicians, 2024)
This study aimed to produce low-fat cookies (C) by substituting Chlorella vulgaris biomass (0.5% CB1, 1.0% CB2, and 1.5% CB3) and investigating the bioavailability of minerals, total phenolic content, and antioxidant capacities of the cookies. Chlorella sp. microalgae is recognized for its high phenolic content, antioxidant capacity, and as a source of essential minerals. Extractable and hydrolyzable fractions were prepared to determine the total phenolic content and antioxidant capacity. The total phenolic content of CB samples ranged from 200.82 to 274.07 mg GAE/g, with bioaccessibility values from 32.31 to 47.26 mg GAE/g. The CUPRAC method provided the highest antioxidant capacity values (116.57-154.38 µmol TE/g), while the ABTS method showed the highest bioaccessibility values (6.76-9.21 µmol TE/g). Mineral content analysis (Na, Mg, P, K, Ca, Mn, Fe, Cu, Zn, and Se) revealed significant enhancements in the CB samples compared to controls, showing an approximate 2-fold increase in mineral bioaccessibility. Despite extensive research on microalgae-fortified foods, there is a notable gap in knowledge regarding their "in vitro bioaccessibility." This study aims to pioneer the exploration of bioaccessibility and highlight the positive impact of algae-based food consumption on human health.
Keywords: Food Sciences (Other); Gıda Bilimleri (Diğer)